2010
DOI: 10.1111/j.1399-0039.2010.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic and haplotypic HLA frequency distribution in Spanish hematopoietic patients. Implications for unrelated donor searching

Abstract: Histocompatibility criteria for unrelated donor selection are based on high-resolution definition of HLA genes. In spite of the expansion of the unrelated donor registries, HLA matching remains a problem for many patients because of the great diversity of HLA alleles and haplotypes. The availability of matched donors at an allelic level depends on the frequency of the patient's alleles and haplotypes. Therefore, data regarding HLA distribution for each population are needed in order to evaluate the donor searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
5
44
1
Order By: Relevance
“…1). Stratification of asymptomatic donors for presence or absence of HSV-1-specific Abs showed that HLA-A*02 was underrepresented solely in seronegative individuals (37.3%), whereas seropositive asymptomatic and symptomatic donors all had A*02 frequencies (52.1 and 49.4%, respectively) similar to those reported in Spanish individuals (45,46), but that difference was only close to significance (p = 0.072 for the comparison between HSV-1 seronegatives and all other donors). Comparison of the HLA allele distribution in the four subgroups of patients showed no other significant differences (Supplemental Table II).…”
Section: Influence Of Hla Diversity On the Outcome Of Hsv-1 Infectionsupporting
confidence: 51%
See 1 more Smart Citation
“…1). Stratification of asymptomatic donors for presence or absence of HSV-1-specific Abs showed that HLA-A*02 was underrepresented solely in seronegative individuals (37.3%), whereas seropositive asymptomatic and symptomatic donors all had A*02 frequencies (52.1 and 49.4%, respectively) similar to those reported in Spanish individuals (45,46), but that difference was only close to significance (p = 0.072 for the comparison between HSV-1 seronegatives and all other donors). Comparison of the HLA allele distribution in the four subgroups of patients showed no other significant differences (Supplemental Table II).…”
Section: Influence Of Hla Diversity On the Outcome Of Hsv-1 Infectionsupporting
confidence: 51%
“…Similarly, we have not considered quantitative differences in the affinity of KIR2DL2 for various HLA-C1, and even -C2, ligands (64). Of note in the latter regard, C*15:02, the predominant C*15 allele in Spain (46,52), encodes a C2 epitope for which KIR2DL2 lacks affinity, and it is recognized with average affinity by KIR2DL1 (64); functional effects of this interaction (e.g., inhibition, education) are yet to be defined. Current data thus provide no clues to understand a possible NK cell-mediated mechanism underlying the observed association of C*15 with HSV-1 infection.…”
Section: Ds2mentioning
confidence: 99%
“…The chronic clinical course in six patients, the lack of response to immunotherapy despite decrease of the antibody levels, and the neuropathological features would favor a primary neurodegenerative disorder. On the other hand, the frequency of HLA-DRB1*1001 and DQB1*0501 among the Spanish population is 1.6% and 14.4%, 24 arguing that the association noted in all four patients with these alleles represents a genetic susceptibility for autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings establish this disorder as a new entity, 1) the characteristic sleep disorder identified in the first three patients by investigators in the Sleep Disorders Unit (masked of information regarding autoantibodies), and in the other five patients by investigators in the Neuroimmunology Laboratory (masked of clinical information)after searching for cases with antibodies similar to those found in the three index patients, 2) the demonstration that patients’ antibodies recognized the same neuronal cell surface antigen (IgLON5), 3) the identification that all patients’ IgLON5 antibodies were mainly IgG4, an isotype considered involved in anti-inflammatory responses, 22 although in some disorders they can be pathogenic, 23 4) the demonstration in 4/4 patients of the same HLA DRB1*1001 and DQB1*0501 alleles which are uncommon among the Spanish population, 24 and 5) the presence of similar neuropathology in two patients, suggesting a novel tauopathy with predominant brainstem and hypothalamic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the risk ratio of the HLA-DRB1*10:01 and HLA-DQB1*05:01 alleles and the development of the anti-IgLON5 disease we compared the frequency of these alleles in the 15 HLA typed patients with the anti-IgLON5 disease and in the Spanish population that presents a similar allele frequency to other Caucasian populations (allelefrequencies.net). 4 Standard protocol approvals, registrations, and patient consents. The ethics committee of the Hospital Clinic approved the study.…”
mentioning
confidence: 99%